Tensile Strength Of Round Bar A 6061 Friction Weld Joint Influenced By Changes Room Temperature - Kido, Muhammad Ikram; Sugiarto, Sugiarto; Darmadi, Djarot B (Sekolah Tinggi Teknologi Adisutjipto, 2019)
Aluminum alloy is non-Ferro material that very difficult to amalgamate using fusion welding, so it requires friction method. Friction welding is process for connecting metals without melting (solid state process), Process merging between the rotating speeds of material forces cause heat friction and at somepoint can be able to melt the materials and melting process occurs. The study aim is to determine tensile strength results from friction weld joints due to changes in ambient temperature of room. Material test is Aluminum A6061. Friction welding uses a lathe with rotation speed of 1600 rpm. The length size of material is 80 mm and 120 mm, diameter 15 mm, Champer angle 15°, 65 bar friction force for 60 seconds, final compressive force 375 bar for 60 seconds and variations in ambient temperature namely room temperature (T0),125 °C,150°C. The A 6061 joint produces the highest tensile strength at temperature 150 oC (188 MPa).